2022
DOI: 10.1111/jonm.13875
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between organizational ethical climate and components of nursing error reporting in selected hospitals of Tehran University of Medical Sciences in 2020

Abstract: Aim:The aim of this study was to investigate the relationship between organizational ethical climate and components of nursing error reporting in selected hospitals of Tehran University of Medical Sciences in 2020.Background: Error reporting is considered as a strategic indicator for error prevention.Method: This is a cross-sectional and correlational study that was conducted on 336 samples who had been selected by stratified random sampling method. Data were analysed by SPSS-16 software, using descriptive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The ethical climate of a hospital can impact midwives’ and nurses’ approach regarding ethical decision-making or ethical dilemmas in the workplace (Jiang et al, 2021) A negative ethical climate can lead to reduced motivation, job performance, and job satisfaction (Lemmenes et al, 2018; Özden et al, 2019; Saygili et al, 2020). It is related to the provision of health services and patient safety (Aly et al, 2020) An improved ethical climate helps to reduce medical errors (Hwang & Park, 2014; Ghasemi et al, 2022) and it has been found to influence job satisfaction, perceived workplace support and commitment (Abou Hashish, 2017) and intent to leave a position. (Barr, 2021) Also, a researcher shows that the perception of ethical work climate directly influences people's decision-making when faced with difficult issues (Shacklock et al, 2013) and it has also been found to be related to moral distress (Abdeen & Atia, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The ethical climate of a hospital can impact midwives’ and nurses’ approach regarding ethical decision-making or ethical dilemmas in the workplace (Jiang et al, 2021) A negative ethical climate can lead to reduced motivation, job performance, and job satisfaction (Lemmenes et al, 2018; Özden et al, 2019; Saygili et al, 2020). It is related to the provision of health services and patient safety (Aly et al, 2020) An improved ethical climate helps to reduce medical errors (Hwang & Park, 2014; Ghasemi et al, 2022) and it has been found to influence job satisfaction, perceived workplace support and commitment (Abou Hashish, 2017) and intent to leave a position. (Barr, 2021) Also, a researcher shows that the perception of ethical work climate directly influences people's decision-making when faced with difficult issues (Shacklock et al, 2013) and it has also been found to be related to moral distress (Abdeen & Atia, 2020).…”
Section: Introductionmentioning
confidence: 99%